Government Collaboration In Managing Clean Water In Permanent Residences In The City Of Palu - Dandan Haryono; Nasir Mangngasing; Nuraisyah; Sisrilnardi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2023)
Abstract Problems related to the availability of clean water for natural disaster survivors living in Permanent Housing (Huntap) in Palu City are still a serious problem that needs to be addressed by the government, especially since this problem has existed since Huntap was occupied by survivors in 2019. The process of resolving public problems related to water Cleaning is no longer the domain of the government, but must be resolved by involving other stakeholders such as the Community, Academics, the Private Sector and the Media. Therefore, this research uses a collaboration modelPenta Helix as a solution to solving clean water problems in Huntap, Palu City. This research uses a descriptive method with a qualitative approach. The informants in this research came from aspectsPenta Helix. The research results confirm that the role of the media and community is significant in monitoring and offering solutions related to clean water management. In this process the involvement of academics is still relatively lacking. In fact, the academic studies carried out can be a reference for the government in overcoming clean water problems in Huntap, Palu City. Keywords: Government Collaboration, Model Penta Helix, Palu City, Permanent Residential, Water Governace.